Pengaruh Return On Asset, Earning Per Share, Debt To Equity Ratio, Dan Current Ratio Terhadap Kebijakan Dividen Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2018 - Lady Claudyna Rahelita Sinaga; Putri Seroja; Annisa Nauli Sinaga (lppm.eka-prasetya.ac.id, 2020)
The research objective is to examine and analyze the effect of Return On Asset, Earning Per Share, Debt to Equity Ratio and Current Ratio on Dividend Policy in manufacturing companies listed on the Indonesia Stock Exchange in the 2016-2018 period. The research approach used in this research is a quantitative approach method. The population to be used in this study were 174 companies, and the sample criteria were assessed using the sampling technique so that 26 companies were obtained as samples. The data translation technique used in this study is multiple linear regression analysis. Based on the results of the hypothesis of the coefficient of determination obtained from the amount of adjusted R square (R2) of 11.5%, it can be denied that Return On Assets, Earning Per Share, Debt to Equity Ratio and Current Ratio have an effect on Dividend Policy by 11.5% while the remaining 88.5% believe in other variables that are not examined in this study